The marine algal flora of the mid-oceanic Azores archipelago: island isolation or Atlantic crossroads? - Tittley, Ian (2013)
5th International Symposium on Fauna and Flora of Atlantic Islands. University College Dublin, República da Irlanda, 24-27 de Agosto de 2004.